2021
DOI: 10.1002/cssc.202101800
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Boride/Boron Carbide Particles Embedded in Boron‐Doped Phenolic Resin‐Derived Carbon Coating on Nickel Foam for Oxygen Evolution Catalysis in Water and Seawater Splitting

Abstract: Electrolysis of seawater can be a promising technology, but chloride ions in seawater can lead to adverse side reactions and the corrosion of electrodes. A new transition metal boride‐based self‐supported electrocatalyst was prepared for efficient seawater electrolysis by directly soaking nickel foam (NF) in a mixture of phenolic resin (PR) and boron carbide (B4C), followed by an 800 °C annealing. During PR carbonization process, the reaction of B4C and NF generated nickel boride (NixB) with high catalytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Li et al. [ 100 ] prepared a new transition metal boride‐based electrocatalyst by placing nickel foam (NF) in a mixed solution of phenolic resin (PR) and boron carbide (B 4 C) and then annealing at 800 °C (Figure 7e). In addition, this catalyst not only can maintain fine OER stability in alkaline seawater (100 mA cm −2 , 24 h) but also shows good corrosion resistance in natural seawater.…”
Section: Non‐noble‐metal‐compound‐based Electrocatalysts For Oxygen E...mentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al. [ 100 ] prepared a new transition metal boride‐based electrocatalyst by placing nickel foam (NF) in a mixed solution of phenolic resin (PR) and boron carbide (B 4 C) and then annealing at 800 °C (Figure 7e). In addition, this catalyst not only can maintain fine OER stability in alkaline seawater (100 mA cm −2 , 24 h) but also shows good corrosion resistance in natural seawater.…”
Section: Non‐noble‐metal‐compound‐based Electrocatalysts For Oxygen E...mentioning
confidence: 99%
“…e) Schematic illustration of the preparation process for Ni x B/B 4 C/B-C PR /NF. Reproduced with permission [100]. Copyright 2021, Wiley.…”
mentioning
confidence: 99%
“…In addition to the effective application for HER, TMCs have also served as effective OER electrocatalysts due to the high electrical conductivity and corrosion resistance in seawater. For instance, Li et al reported facile immersion and calcination method for the fabrication of Ni x B/B 4 C, which was transformed from the precursors of the phenolic resin and boron carbide, as shown in the Figure 8A 86 . The SEM and TEM image showed the morphology of such catalyst (Figure 8B‐D), which exhibited nano‐sized particles (Figure 8C).…”
Section: Tm‐based Electrocatalysts For Driving Seawater Electrolysismentioning
confidence: 99%
“…For instance, Li et al reported facile immersion and calcination method for the fabrication of Ni x B/B 4 C, which was transformed from the precursors of the phenolic resin and boron carbide, as shown in the Figure 8A. 86 The SEM and TEM image showed the morphology of such catalyst (Figure 8B-D), which exhibited nano-sized particles (Figure 8C). Typically, the B-doped carbon layer not only fixed the Ni x B/B 4 C nano-sized particles, but also played important role of the transport for electrons.…”
Section: Transition Metal Carbidesmentioning
confidence: 99%
See 1 more Smart Citation